Anesthetic management of a patient with dilated cardiomyopathy by combined spinal-epidural anesthesia (case report) (Annals of Medical Research, 2021)
None
Keywords: s : Caesarean section, dilated cardiomyopathy, combined spinalepidural anesthesia